KEANEKARAGAMAN DAN KEKERABATAN IKAN FAMILI CYPRINIDAE PADA EKOSISTEM BENDUNGAN COLO SUKOHARJO JAWA TENGAH - Ragil Nur Cahyono; Agung Budiharjo; Sugiyarto Sugiyarto (EnviroScienteae, 2018)
The Cyprinidae fish family is a family of freshwater fish with the largest number of species and its presence is widespread almost all of the world. The main habitat of this family is the river's ecosystem, river damming changing the environmental conditions between the ecosystems before and after the dam's watergate. Such as Colo Dam that dammed Bengawan Solo River that allegedly affects the diversity of species of Cyprinidae fish. So this study was conducted in order to determine the diversity and kinship of the Cyprinidae fish family in the ecosystem before and after the Colo Dam watergate. Sampling was conducted September-October 2017 at Sukoharjo Colo Dam by Purposive sampling method. Identify fish species used Kottelat identification books. The diversity of fish species was calculated by Shannon Wiener's diversity index. The correlation between abiotic factor and fish diversity was analyzed by a regression test. The kinship of the fish was analyzed by the Ntsys cluster method (2.02i). The results showed that the Cyprinidae fish species that live in the Colo Dam ecosystem contain 10 species, the diversity of Cyprinidae fish in the fast-water ecosystem of station I is higher (0,96) then the slow-water ecosystem of station II, III, and IV (0,47; 0,73, and 0,58). Abiotic factors of current velocity affect the level of fish diversity reaches 91%. The Cyprinidae fish kinship rate has a coefficient of resemblance between 60% - 85%, fish with the same genus and many similarities in morphological characters and their behavior is categorized as having a close kinship.